TINJAUAN HUKUM ISLAM TERHADAP PEMBAYARAN GANTI RUGI MATERIIL NAFKAH BATIN SUAMI ISTRI YANG TIDAK TERPENUHI - Halmi Abdul Halim (Al Ahkam, 2021)
Marriage is a bond between a man as husband and woman as wife. Due to the bond between two people, according to civil principles, rights and obligations will arise. The rights and obligations of husband and wife have been regulated in the Marriage Law and the Compilation of Islamic Laws, one of which is the husband's obligation to provide for his wife. Nafkah can be divided into two, namely physical and mental income. Regarding the fulfillment of the inner income that is not fulfilled, it is used as an object for requesting payment of material compensation. This has not been regulated in statutory regulations. Then after being viewed from the perspective of Islamic law, there are no rules that regulate it. Keywords: Inner Life; Material Compensation; Islamic Law